Efektivitas Assertive Training Sebagai Strategi Transformatif Terhadap Self-Confidence Siswa - Bin Anuar, Arman; Fahmi, Ainul; Edison, Edison; Samsaifil, Samsaifil (UPT Publikasi dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2024)
Declining student self-confidence is still a significant problem in the educational landscape, affecting academic achievement, social interaction, and psychological well-being. This study investigates the effectiveness of assertive training as a transformative intervention to increase self-confidence among students at SMAN 2 Palopo. The study, employing a one-group pretest-posttest experimental design, focused on 30 students specifically selected for their low self-confidence. The study used observation, a self-confidence scale, and assertive quizzes as data collection methods. Statistical analysis using paired t-tests revealed a significant increase in post-training confidence (p < 0.001), with 53.3% of students categorized as having high self-confidence and 26.7% very high. These results underscore the capacity of assertive training to change students' self-perception and improve assertive communication skills. The study concluded that integrating assertive training into school counseling programs can sustainably foster students' psychological and social development. We suggest future research to explore the long-term effects and adapt the intervention into diverse educational contexts. ____________________________________________________________________Penurunan self confidence siswa masih menjadi masalah yang signifikan dalam lanskap pendidikan, yang memengaruhi prestasi akademik, interaksi sosial, dan kesejahteraan psikologis. Studi ini menyelidiki efektivitas assertive training sebagai intervensi transformatif untuk meningkatkan rasa percaya diri di kalangan siswa di SMAN 2 Palopo. Dengan menggunakan desain eksperimen One-Group Pretest-Posttest, penelitian ini melibatkan 30 siswa yang dipilih secara sengaja yang diidentifikasi memiliki rasa percaya diri yang rendah. Metode pengumpulan data meliputi observasi, skala self confidence, dan kuis asertif. Analisis statistik menggunakan uji-t berpasangan mengungkapkan peningkatan yang signifikan dalam rasa percaya diri pasca pelatihan (p < 0,001), dengan 53,3% siswa dikategorikan memiliki rasa percaya diri yang tinggi dan 26,7% sangat tinggi. Hasil ini menggarisbawahi kapasitas pelatihan asertif untuk mengubah persepsi diri siswa dan meningkatkan keterampilan komunikasi asertif. Studi ini menyimpulkan bahwa mengintegrasikan pelatihan asertif ke dalam program konseling sekolah dapat secara berkelanjutan membina perkembangan psikologis dan sosial siswa. Penelitian di masa mendatang disarankan untuk mengeksplorasi efek jangka panjang dan mengadaptasi intervensi ke dalam konteks pendidikan yang beragam.